2019
DOI: 10.1109/access.2019.2901966
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Integral-Type Terminal Sliding Mode Fault Tolerant Control for Spacecraft Attitude Tracking

Abstract: In this paper, the attitude tracking control for a spacecraft system based on a novel adaptive integral-type terminal sliding mode fault-tolerant control strategy is investigated. First, a basic fault-tolerant control scheme is designed to ensure the spacecraft attitude tracking performance in the presence of the actuator fault, external disturbance, and actuator saturation when the rotational inertia of a spacecraft system is known. Second, combined with adaptive laws, a modified fault-tolerant control scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…Hence it is required to convert (40) into a similar linearized form, so that an equivalent of equations (28), (29) and (38) can be derived for output level as well. For that, we first examine (25) and write it in a general form:…”
Section: A Smc For Level Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence it is required to convert (40) into a similar linearized form, so that an equivalent of equations (28), (29) and (38) can be derived for output level as well. For that, we first examine (25) and write it in a general form:…”
Section: A Smc For Level Controlmentioning
confidence: 99%
“…The terminal SMCs have a shortcoming that the control law may face the problem of singularity, which causes unbound growth of control inputs. This singularity issue has been dealt with different approaches [23]- [25]. However, all nonlinear manifold SMCs and especially terminal SMCs have the same problem, i.e., they use complex formulations of manifolds, which does not solve the problem of the design process for complex nonlinear models.…”
Section: Introductionmentioning
confidence: 99%
“…However, the system disturbances are inevitable which intensively interfere with the system stability and transient performance. Among the exiting control techniques, sliding mode control (SMC) is an efficient robust control approach [14] which is widely used in many field such as spacecraft [15], linear motor [16] and MEMS gyroscope [17].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical analysis and simulation results showed that the designed controller can make the system converge to a small domain near the origin in finite time. In [26], the attitude-tracking problem of rigid spacecraft was addressed. With the control allocation technique and SMC technique, an adaptive sliding mode fault-tolerant controller was developed, which can eliminate the effects of actuator faults, mass and inertia uncertainties, and unknown external disturbances.…”
Section: Introductionmentioning
confidence: 99%